After Ripening Period Impacts the Seed Germination of Berseem - MAITY A; SANJAY KUMAR (Seed Research, 2026)
An experiment was set up to identify the minimum duration of seed storage after harvest for completion of after-ripening processes in berseem seeds (Trifolium alexandrinum). The fresh seeds of three berseem cultivars were stored under ambient conditions for 0, 30, 60, 90, 120, 150, 180, 210 and 240 days after harvest (DAH). At the end of each storage period, the seeds were tested for germination. All the three cultivars of berseem had 40-55% germination immediately after harvest maturity, which indicated medium level of seed dormancy. The after-ripening period significantly enhanced the germination of all the berseem cultivars up-to 150 DAH. Wardan and Bundel Berseeem -2 showed 80% germination (required for certified seed of berseem by Indian Minimum Seed Certification Standard (IMSCS) at only 60 DAH whereas, whereas Bundel Berseeem -3 seed took 120 days to reach at standard germination (80%). Higher fraction of dead seeds than dormant seeds across all cultivars were observed after 240 DAH, which indicates the complete breakdown of seed dormancy. The results of this experiment can help plan the time of seed testing and planting for full realization of the germination potential of berseem cultivars under subtropical conditions.